Trajetórias e saberes docentes na concepção sobre uso de tecnologias digitais no ensino superior: o caso da URI-Campus Frederico Westphalen/RS - Candaten, Fernanda Borguezan (Universidade do Vale do Rio do Sinos, 2006)
This research is linked to the Line Pedagogic "Practices and Formation of the Educator", from the Program of Masters degree in Education of the University of the Vale do Rio dos Sinos - UNISINOS. The theme is related to the Digital Technologies - TDs in the Higher education, having as focus the teachers' conception in relation to the use of those technologies in their pedagogic practices. The problem consists on investigating how the paths are constituted and in what way the teaching learnings are articulate in the conceptions about the use of TDs in the pedagogic practices developed by teachers that act in the Higher education of URI - Campus de Frederico Westphalen/RS. From the problem are derived the following subjects: which are the teachers' paths that use TDs in their pedagogic practices? What knowledges are articulate in the constitution of the conceptions in relation to the pedagogic practices with the use of TDs? How the teachers understand the concept of TDs? Which is the conception of paradigm
Keywords: avaliação didática; ensino superior; formação; profissão; tecnologia digital; professor universitário; Conceptions; digital technologies; Pedagogic practices; TDs; teaching knowledges; paths; Ciências Humanas